A fully biodegradable polydioxanone occluder for ventricle septal defect closure - Zefu Li; Pengxu Kong; Xiang Liu; Shuyi Feng; Wenbin Ouyang; Shouzheng Wang; Xiaopeng Hu; Yongquan Xie; Fengwen Zhang; Yuxin Zhang; Rui Gao; Weiwei Wang; et al. (Bioactive Materials, 2023)
Ventricular septal defect (VSD) is one of the commonest congenital heart diseases (CHDs). Current occluders for VSD treatment are mainly made of nitinol, which has the risk of nickel allergy, persistent myocardial abrasion and fatal arrythmia. Herein, a fully biodegradable polydioxanone (PDO) occluder equipped with a shape line and poly-l-lactic acid PLLA membranes is developed for VSD closure without the addition of metal marker. PDO occluder showed great mechanical strength, fatigue resistance, geometry fitness, biocompatibility and degradability. In a rat subcutaneous implantation model, PDO filaments significantly alleviated inflammation response, mitigated fibrosis and promoted endothelialization compared with nitinol. The safety and efficacy of PDO occluder were confirmed in a canine VSD model with 3-year follow-up, demonstrating the biodegradable PDO occluder could not only effectively repair VSD, induce cardiac remodeling but also address the complications associated with metal occluders. Furthermore, a pilot clinical trial with five VSD patients indicated that all the occluders were successfully implanted under the guidance of echocardiography and no adverse events occurred during the 3-month follow-up. Collectively, the fully bioresorbable PDO occluder is safe and effective for clinical VSD closure and holds great promise for the treatment of structural CHDs.